Propriedades bioativas e composição fenólica de Lotus spp - Flores, Ricardo Antunes (2018)
Lotus spp. represents an important kind among the leguminous pastures in the south of Brazil. Among its characteristics, the presence of diverse secondary metabolites stands out, such as tannins, phenolic acids and flavonoids, which may be responsible for many benefits to the animal and human organisms, representing an important product for the genetic improvement and, consequently, for the pharmaceutical industry. Seeking to pursue this theme, this work had the overall goal of evaluating if there is an intra and interspecific variability in Lotus spp. related to the phytochemical composition and bioactive properties. In order to achieve that, four cultivars of the Lotus kind were selected, with two of them being of the Lotus corniculatus L. species (UFRGS and São Gabriel) and two of them of the Lotus uliginosus Schkuhr. species (Maku and Serrano). For the execution of the research, four experiments were carried out, with Experiment 1 evaluating two tannin monomers in CLAE (gallocatechin and epigallocatechin) in w hich the evaluated parameters were the ones of linearity, detection limit, quantification limit, precision, accuracy, and robustness. Experiment 2 aimed to quantify the concentration of tannin monomers, phenolic acids and a flavonoid in the four cultivars mentioned before, in two phonological stages. Experiment 3 evaluated the antimicrobial (antibacterial and antifungal) of six fractioned extracts, obtained in the cultivars mentioned before, which were tested for Enterococcus faecalis, Escherchia coli, Streptococcus mutans, Candida albicans and Penicilium sp. through the tests of disk-diffusion and microdilution. Experiment 4 evaluated the cellular viability, using five extracts and seven concentrations, before the cellular lineage of the bovine kidney (MDBK ). The results showed that, regarding the catechin and epicatechin concentration, the cv. UFRGS presented the best levels on both phenological stages, as well as cv. Serrano, which presented the best gallocatechin and epigallocatechin relationship. Regarding the concentration of the phenolic acid monomers, cv. São Gabriel presented the highest levels within the two phenological stages assessed. For the rutin flavonoid, cv. Maku presented 0,161 g/kg of dry mass in the vegetative stage and, in the flowering state, cv. São Gabriel presented 1,3 g/kg of dry mass. Regarding the antibacterial test, all extract fractions presented inhibition, but the cv. UFRGS was the most bioactive for E. faecalis, while for the E.coli, the Serrano cultivar presented the best leve ls of inhibition of bacterial growth. Regarding the antifungal activity, the raw extracts, the ethyl and aqueous acetate of cv. São Gabriel presented the best levels of growth inhibition for the C. albicans, while cv. Maku stood out in the hexane extract and the Serrano cultivar in the dichloromethane extract. Regarding the cellular viability test, cv. São Gabriel presented cytotoxic concentration in the hexane, dichloromethane and butanol fractions, while the extracts of the ethyl acetate fraction of all cultivars did not present any toxic action to the MDBK cells. Therefore, it was concluded that the cultivars of the Lotus spp. type evaluated presented intraspecific differences for all assessed criteria.